Hanri Bergson and Vladimir Nabokov’s Concept of Memory - A.E. Shapiro (Язык и текст, 2016)
The article looks at common aspects and differences in the understanding of the concept of memory in «Ada or Ardor: A Family Chronicle», «Transparent Things» by Vladimir Nabokov and «Matter and Memory» by Hanri Bergson. Main memory functions as interpreted by the two authors are analyzed.